2022
DOI: 10.2166/wcc.2022.323
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of water balance and hydrodynamics of Lake Beseka, Ethiopia

Abstract: This study aims to calculate the water balance, interaction with irrigation water inflow, and hydrodynamics of the Lake Beseka by a spreadsheet-based model using climatic, hydrological, multi-temporal satellite images, groundwater, and lake chemistry data. The rainfall for the catchment was estimated as 558.4 mm/year, whereas the mean evaporation was computed as 2,214 mm/year by the Penman method. The annual direct rainfall contribution to the lake was obtained to be 25.84 MCM (million cubic meters) and a runo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Before being used for data analysis, it is necessary to validate and correct TRMM rainfall data for 2000 -2019 with observation posts using the Correlation Coefficient method which produces a determination value and continues data correction by selecting the regression equation with the highest determination value. The regression equation used is linear, geometric, logarithmic, and exponential regression (Gichamo et al, 2022;Ezuar et al, 2018). The criteria for the determination value (R2) according to Setyorini & Hardaningrum (2020), is a very low interpretation is 0.00-0.199, Low is 0.20-0.399, moderate is 0.40-0.599, strong is 0.60-0.799 and very strong is 0.80-1.000.…”
Section: Methodsmentioning
confidence: 99%
“…Before being used for data analysis, it is necessary to validate and correct TRMM rainfall data for 2000 -2019 with observation posts using the Correlation Coefficient method which produces a determination value and continues data correction by selecting the regression equation with the highest determination value. The regression equation used is linear, geometric, logarithmic, and exponential regression (Gichamo et al, 2022;Ezuar et al, 2018). The criteria for the determination value (R2) according to Setyorini & Hardaningrum (2020), is a very low interpretation is 0.00-0.199, Low is 0.20-0.399, moderate is 0.40-0.599, strong is 0.60-0.799 and very strong is 0.80-1.000.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike other rift valley lake watersheds, the catchment of the Lake Beseka does not contain perennial river that drains into the lake, except seasonal floods in the wet season, in addition to excess irrigation drainage and groundwater inflow [89]. The lake was essentially a surface pond of about 2.7 km 2 total surface area in the late 1950's and early 1960's before the establishment of Metahara Sugar Estate [7,97].…”
Section: Lake Besekamentioning
confidence: 99%
“…Although the starting time of expansion is not exactly known, most previous studies tend to agree that the problem was initiated in the late 1960 and early 1970s when the Metahara mechanized farm around the lake was started to be irrigated for cultivation of cotton and citric fruits which latter on shifted to sugarcane development [7,12,85,97,98]. Furthermore, [89] reported that the water level of Lake Beseka started to rise from 1976 to 1978 as a result of poor irrigation water management practices of the newly introduced Abadir farm.…”
Section: Lake Besekamentioning
confidence: 99%
See 1 more Smart Citation